FLOUTING MAXIMS IN “BEAUTY AND THE BEAST” MOVIE - Safrida Florentina; Ambalegin Ambalegin (Asosiasi Ide Bahasa Kepri, 2021)
Communication is one of important part in human life. This research related to the phenomenon of pragmatics. This research focused on analyzing the flouting of maxims in the Disney film entitled “Beauty and the Beast”. The purpose of this study is to determine the kinds of maxim flouting produced by the actor. For this research, the researchers used Grice's theory of flouting maxim. This research used descriptive qualitative as the research design which shapes how the report of the analysis would be descriptively. This research collected the data by applying observational and non-participatory technique by Sudaryanto (1993). As for analyzing data, the researchers used pragmatic identity method and pragmatic competence- in equalizing technique. From the analysis of the collected data, the researchers found that several conversations of the main characters in this film contained flouting of the maxims. Those were 4 data of maxim quantity, 4 data of maxim quality, 3 data of maxim of relevance, and 2 data of maxims manner.